2017
DOI: 10.1001/jamacardio.2017.2671
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neighborhood Demographics With Out-of-Hospital Cardiac Arrest Treatment and Outcomes

Abstract: Those with OHCA in predominantly black neighborhoods had the lowest rates of bystander cardiopulmonary resuscitation and automatic external defibrillation use and significantly lower likelihood for survival compared with predominantly white neighborhoods. Improving bystander treatments in these neighborhoods may improve cardiac arrest survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 33 publications
3
89
0
Order By: Relevance
“…However, our calculated survival rates did not indicate a statistically significant difference in OHCA survival for blacks compared with other groups. This contrasts with other studies and may be related to our relatively small sample size, our single‐city analysis, lack of geographic analysis, and limited availability of clinical and social variables 28, 33. In the future, our ongoing data collection will allow us a thorough exploration of this issue.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, our calculated survival rates did not indicate a statistically significant difference in OHCA survival for blacks compared with other groups. This contrasts with other studies and may be related to our relatively small sample size, our single‐city analysis, lack of geographic analysis, and limited availability of clinical and social variables 28, 33. In the future, our ongoing data collection will allow us a thorough exploration of this issue.…”
Section: Discussionmentioning
confidence: 79%
“…One recent study by Starks et al found that OHCA patients living in majority‐black neighborhoods had lower survival rates to hospital discharge 28. Residential segregation between blacks and other groups is extremely high in Detroit, and this segregation is associated with racial health disparities and high black mortality 29, 30, 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…A large US cohort study (n = 14,225) showed that patients who had an OHCA in low-income black neighbourhoods were less likely to receive bystander-initiated CPR than those in highincome white neighbourhoods [21]. This was confirmed in a recent study which documented that the lowest rates of bystander CPR and AED use occurred in predominantly black neighbourhoods, and that these neighbourhoods had a significantly lower likelihood for OHCA survival compared with predominantly white neighbourhoods [22]. Improving bystander interventions in these neighbourhoods may improve cardiac arrest survival.…”
Section: Variations In Community Responsementioning
confidence: 81%
“…The mechanisms of the observed variation in our study are likely multifactorial, including unmeasured patient-level factors (eg, comorbidity 9 and first-responder interventions), EMS-level factors (eg, experience and training of EMS personnel), 28 hospital-level factors (eg, practice variation in timing of withdrawal of life-sustaining therapy 29 and receiving hospital characteristics 30 ), and neighborhood-level factors (eg, racial/ethnic composition). 31 We found that in all survival quartiles of EMS agencies, median chest compression fraction exceeded 0.80, and median chest compression rate was between 100 and 120 compressions per minute. Both metrics conform with current evidence-based practice guidelines.…”
Section: Discussionmentioning
confidence: 69%